THE VALUE OF THE MAHALLA, NATIONAL TRADITIONS, AND CULTURAL HERITAGE IN THE PROCESS OF GLOBALIZATION (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the impact of globalization processes on the mahallainstitution and its role in preserving national values, traditions, and cultural heritage. Inthe context of global cultural influences, the study highlights the socio-cultural functionsof the mahalla and its importance in transmitting customs and traditional values fromgeneration to generation. Special attention is paid to the transformation of the mahallainstitution in the contemporary global environment, its potential in maintaining nationalidentity, and the challenges it faces. The article presents scholarly conclusions andrecommendations aimed at strengthening the role of the mahalla in preserving nationalcultural heritage and ensuring social stability
Keywords: globalization; mahalla institution; national values; national traditions; cultural heritage; socio-cultural life; national identity; social stability